How Good at Neurology are you? – Answers. Issue 2 (1st April 2003) - Goldsmith, Paul; Lennox, Graham; Ray, Julian
Abstract : 1. (d) (HIT) HIT or heparin induced thrombocytopenia, is divided into type I and II. Type I consists of a mild non-immune thrombocytopenia, often seen within a few days of starting heparin. This is typically transient, requires no intervention and improves despite continued heparin administration. Type II, in contrast, is an immune-mediated, idiosyncractic reaction with potentially severe consequences. Severe thrombocytopenia with haemorrhage, purpura and a platelet count of less than 20, is uncommon, with the complications coming mainly from the associated thrombotic tendency. Both arterial and venous thromboses occur. The thromboses may be seen even with a 'normal', albeit falling platelet count. Onset is usually 5–14 days after starting heparin, but can occur earlier if there has been previous heparin exposure. HIT may also occur with low molecular weight heparin, albeit more rarely. Treatment is to stop the heparin and give an alternative anticoagulant. PNH: paroxysmal nocturnal haemoglobinuria. Chronic